Remarks by David Freestone. (22nd March 2019) - Freestone, David
Abstract : As a teacher of international law for more years than I care to admit, I have to declare at the start of my comments that I admire the South China Sea Arbitration Award greatly. It presents an interpretation of the provisions of the 1982 UN Convention on the Law of the Sea (UNCLOS) on islands and rocks in a comprehensive, carefully considered and intellectually satisfying way. As my colleagues will doubtless point out, it does present problems relating to current existing state practice, but it does to my mind capture what the UNCLOS III drafters had in mind when the 1982 Convention text was put together.